2023
DOI: 10.3390/polym15030611
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Sound Insulation Performance of Composite Rubber Reinforced with Hollow Glass Microsphere Based on Acoustic Finite Element Simulation

Abstract: The composite rubber reinforced with hollow glass microsphere (HGM) was a promising composite material for noise reduction, and its sound insulation mechanism was studied based on an acoustic finite element simulation to gain the appropriate parameter with certain constraint conditions. The built simulation model included the air domain, polymer domain and inorganic particles domain. The sound insulation mechanism of the composite material was investigated through distributions of the sound pressure and sound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 53 publications
0
5
0
Order By: Relevance
“…Taking the optimized structure for the target frequency ranges of 650-1150 Hz as an example, the sound absorption mechanism of the hexagonal acoustic metamaterial cell was revealed by the distributions of the sound pressure for the various resonance frequency [54][55][56][57], as shown in Figure 10. The 11 resonance frequencies were 664 Hz, 689 Hz, 737 Hz, 791 Hz, 836 Hz, 882 Hz, 920 Hz, 962 Hz, 1011 Hz, 1080 Hz and 1140 Hz.…”
Section: Sound Absorption Mechanismmentioning
confidence: 99%
“…Taking the optimized structure for the target frequency ranges of 650-1150 Hz as an example, the sound absorption mechanism of the hexagonal acoustic metamaterial cell was revealed by the distributions of the sound pressure for the various resonance frequency [54][55][56][57], as shown in Figure 10. The 11 resonance frequencies were 664 Hz, 689 Hz, 737 Hz, 791 Hz, 836 Hz, 882 Hz, 920 Hz, 962 Hz, 1011 Hz, 1080 Hz and 1140 Hz.…”
Section: Sound Absorption Mechanismmentioning
confidence: 99%
“…Thirdly, there have been many studies mainly investigating sound-insulation performance by numerical simulation without any experimental validations [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. For example, a versatile and fully coupled technique based on the finite-element–boundary-element model was developed by Sahu et al [ 52 ], and the contributions of the individual components in transmitted energy were identified by numerical simulations.…”
Section: Resultsmentioning
confidence: 99%
“…It was presented by Fan et al [ 53 ] that theoretical analysis and finite element simulation demonstrated that an acoustic metamaterial based on membrane-coated perforated plates can effectively block acoustic waves over a wide low-frequency band regardless of incident angles. In the literature [ 54 ], composite rubber reinforced with hollow glass microspheres was considered a promising composite material for noise reduction, and its sound-insulation mechanism was studied based using an acoustic finite element simulation to obtain the appropriate parameters with certain constraint conditions. Kim [ 55 ] conducted a numerical simulation of sound-transmission loss for a double-panel structure with sonic crystal composed of distributed local resonators, and the results showed that the sound insulation could be significantly improved in the low-frequency range while reducing the total mass without increasing the thickness.…”
Section: Resultsmentioning
confidence: 99%
“…Taking the distributions of the total sound energy density (TSED) around the effective sound absorption band for MCAM-MNCs-1 with the various depths of chamber T as the object, the sound absorption mechanism of MCAM-MNCs was revealed, which was obtained by the acoustic finite element simulation [44,45].…”
Section: Mechanism Investigationmentioning
confidence: 99%
“…Therefore, it further proved that the parameters of MCAM-MNCs should be reasonably selected for the expected sound absorption band, which included the diameter of aperture d, the depth of chamber T 0 , and the thickness of panel t 0 in this study. as the object, the sound absorption mechanism of MCAM-MNCs was revealed, which was obtained by the acoustic finite element simulation [44,45].…”
Section: T = 30 MMmentioning
confidence: 99%